2009
DOI: 10.3136/fstr.15.95
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Some Phanerogam Plant Extracts

Abstract: Nine phanerogam plants (common lady's-mantle, bear's garlic, common sweet flag, agrimony, goldenrod, common speedwell, european mistletoe, horsetail and milfoil) were evaluated regarding their total flavonoid contents and antioxidant activity. The flavonoid contents ranged from 0.72 (goldenrod) to 0.25 mmol/g dry matter (horsetail). The contents of quercetin, rutin, kaempferol and myricetin were quantified by high performance liquid chromatography. Quercetin content was found to be very low in goldenrod and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…These compounds have been widely studied and used in different areas. Flavones are part of the antioxidants that control oxidation processes by eliminating free radicals [ 44 ]. Specifically, flavones from Asian mistletoe genera with antimicrobial and hypotensive properties were reported [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been widely studied and used in different areas. Flavones are part of the antioxidants that control oxidation processes by eliminating free radicals [ 44 ]. Specifically, flavones from Asian mistletoe genera with antimicrobial and hypotensive properties were reported [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that in mistletoe hosted by Malus domestica, the main compound was rosmarinic acid (17.48 mg %), while in mistletoe hosted by Populus nigra, the dominant component was chlorogenic acid (12.34 mg %). Condrat et al (2009) investigated also nine phanerogam plants (including the european mistletoe) for their flavonoid content and antioxidant activity. Quercetin and kaempferol concentrations were found to be very low in mistletoe extracts (0.20 µmol/g dry matter, and 0.16 µmol/g dry matter, respectively).…”
Section: Dpph Inhibition By Mistletoe Extractsmentioning
confidence: 99%
“…Flavones are another group of compounds found in Mexican mistletoes [ 6 ]. These phytochemicals have been studied and widely used in different areas, and are part of the antioxidants involved in oxidation processes by eliminating free radicals [ 23 ]. In mistletoes of the Asian genus, flavones have been found with the capacity to reduce the presence of microorganisms such as fungi and bacteria, in addition to reducing blood pressure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%